The Application of Penal Mediation in Handling Minor Criminal Offenses Regulated by Regional Regulations - Fandri Rachmanto (JUSTISI, 2025)
This study aims evaluates the effectiveness of penal mediation in resolving minor offenses under Regional Regulations (Perda) in Indonesia, focusing on reducing court caseloads and aligning with national and local legal frameworks. This study A normative legal research method was used, analyzing primary legal materials, such as laws and judicial decisions, supplemented by secondary sources, including case studies. A comparative analysis was conducted with New Zealand’s restorative justice system. Novelty The research highlights the integration of penal mediation within Perda as a tailored approach for minor offenses. It identifies challenges such as regional disparities, limited mediator availability, and insufficient public awareness, offering strategic recommendations. Findings Penal mediation effectively resolves minor offenses by emphasizing dialogue and accountability. However, inconsistent mediator training and lack of institutional support remain key challenges. Conclusion Penal mediation is an effective alternative for minor offenses under Perda. Its success depends on public awareness, standardized training, and institutional support. Lessons from international best practices can help optimize its implementation.